Kajian Aktivitas Berdasarkan Kondisi Lingkungan pada Kawasan Tepian Sungai Cikapundung - Almira Ulfa; Harrini Mutiara Hapsari; Sri Lilianti Komariah; Rizka Drastiani (Archvisual: Jurnal Arsitektur dan Perencanaan, 2024)
The Riverside area has the potential to be developed into an interactive public space. The exciting thing about it is doing activities in places close to the water while enjoying its beauty and atmosphere. This study identifies activities in the Cikapundung River bank area, including necessary, optional, and social activities. Then, it was also identified whether the community involved the Cikapundung River bank area when carrying out the optional and social activities. The method used is qualitative research, using interviews and field observation. The results show that people who live directly adjacent to the river carry out activities with solid interactions with the Cikapundung River. Meanwhile, settlement areas close to the river but not directly adjacent have minimal interaction with the river. It was found that the location and the openness to the river greatly influenced whether or not people interacted with the river. The output of this study can be a basis for developing areas along river banks.